Hybrid Nuclear Power Plants: Integration with Renewable Energy Sources - Sherzod S. Djumanov; Asalkhon Z. Norkhujayeva (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
emissions, one of the key challenges remains ensuring the reliability of energy systems while integrating renewable energy sources (RES). Traditional energy sources, including coal and gas power plants, have a significant impact on the environment, whereas complete decarbonization of energy systems requires transitioning to hybrid generation schemes. The development of RES, particularly wind power plants (WPPs), significantly reduces the carbon footprint. However, their variable nature leads to power fluctuations, complicating energy system balancing. Modern solutions based on battery energy storage systems have limitations in terms of storage duration and high costs, necessitating the search for new technological approaches. The study of nuclear-renewable hybrid systems is a relevant scientific and technical challenge aimed at developing sustainable, safe, and economically efficient solutions for the future global energy system. Implementing such systems will help achieve a balance between stable baseload generation and the environmental benefits of RES, which is particularly crucial amid growing energy demand and the transition to a carbon-neutral economy. Aim: to analyze the concept of hybrid nuclear power plants (NPPs), examine possible schemes for their integration with renewable energy sources (RES), identify their advantages and limitations, and discuss promising technologies such as small modular reactors (SMRs) and energy storage systems (ESS). Methods: this article presents an analytical review of existing and emerging technologies for integrating nuclear power plants (NPPs) with renewable energy sources (RES). The study includes a comparative analysis of different hybrid energy system implementation schemes, an examination of the technical characteristics and economic feasibility of small modular reactors (SMRs), and an assessment of modern energy storage systems (ESS). The research is based on scientific publications, reports from international energy agencies, and data on innovative projects in the field of hybrid energy systems. Results: The analysis demonstrated that hybrid NPPs offer several advantages over traditional energy systems, including increased energy supply resilience, reduced carbon footprint, and enhanced generation flexibility. Small modular reactors (SMRs) have shown the highest potential in combination with RES due to their high controllability and modularity. Moreover, the use of energy storage systems, such as battery storage, pumped hydro storage, and hydrogen technologies, contributes to efficient energy flow management.